THE RELATIONSHIP OF INTRINSIC GOAL ORIENTATION FOR LEARNING GEOGRAPHY, SELF-EFFICACY FOR LEARNING AND PERFORMANCE IN GEOGRAPHY, AND METACOGNITIVE SELF-REGULATED GEOGRAPHY LEARNING WITH BHUTAN GEOGRAPHY ACHIEVEMENT OF GRADE 8 STUDENTS AT DRUK HIGHER SECONDARY SCHOOL IN THIMPHU, BHUTAN - PELDON, SONAM; LYNCH, RICHARD (Scholar: Human Sciences, 2022)
The study aimed to determine whether there was a significant relationship between intrinsic goal orientation for learning geography, self-efficacy for learning and performance in geography, and metacognitive self-regulated geography learning with Bhutan geography achievement of Grade 8 students at Druk Higher Secondary School in Thimphu, Bhutan. The Motivated Strategies for Learning Questionnaire (MSLQ; Pintrich et al., 1991) was adapted and used to collect the data on intrinsic goal orientation for learning geography, self-efficacy for learning and performance in geography, and metacognitive self-regulated geography learning from 49 Grade 8 students at Druk Higher Secondary School in Thimphu, Bhutan in Term 2 of the Academic Year 2020. A total of 49 students from Grade 8 were selected using the convenience sampling method for the research conducted. The Bhutan Geography achievement scores of the students were collected using the End of Term 2 Bhutan geography examination. A correlational analysis was used to determine the relationships of intrinsic goal orientation for learning geography, self-efficacy for learning and performance in geography, and metacognitive self-regulated geography learning and Bhutan geography achievement of the Grade 8 students. The relationship between intrinsic goal orientation and Bhutan geography achievement was weak but positively correlated. The relationship between self-efficacy for learning and performance in geography and Bhutan geography achievement; and the relationship between metacognitive self-regulated geography learning and Bhutan geography achievement was moderately strong. The findings further indicated that there was a significant, moderately strong, and positive 1 Lecturer, Royal Thimphu College, Thimphu-Bhutan. sonampeldon@rtc.bt 2 Ph.D., Assistant Professor, Graduate School of Human Sciences, Assumption University, Thailand. richardlynch2002@yahoo.com Scholar: Human Sciences, ISSN 2586-9388, Vol.14 No.2 (Jul.-Dec. 2022) 447 correlation between the three independent variables and one dependent variable. Recommendations for students, teachers, curriculum developers, and future research are provided.